Procurement planning factors influencing the quality performance of primary healthcare building facilities: A mediation effect of the firm's business partnership. Issue 1 (1st January 2021) - Gambo, Nuru; Musonda, Innocent
Abstract: The paper reports on an assessment of the mediation effect of a firm's business partnership on procurement planning factors influencing the quality performance of primary healthcare building facilities. A quantitative data collection approach was adopted in the study using structured questionnaires circulated to 520 respondents comprising project managers in the Nigerian construction industry. A stratified proportionate random sampling method was used for the selection of respondents which yielded 370 responses and 357 were used for analysis. Findings were that procurement planning factors influenced the quality performance of primary healthcare building facilities, and the firm's business partnerships mediate the relationship between procurement factors and quality performance of primary healthcare building facilities. This study serves as awareness to governments and other stakeholders in the construction industry on the provision of quality primary healthcare building facilities by leveraging a firm's business partnership as a mediating factor. Findings show that the relationship would enhance the rapid provision of quality healthcare building facilities for the growing population of Nigeria and other developing countries facing similar shortages of quality healthcare building facilities.